2016
DOI: 10.1002/sim.7182
|View full text |Cite
|
Sign up to set email alerts
|

Estimating personalized diagnostic rules depending on individualized characteristics

Abstract: There is an increasing demand for personalization of disease screening based on assessment of patient risk and other characteristics. For example, in breast cancer screening, advanced imaging technologies have made it possible to move away from “one-size-fits-all” screening guidelines to targeted risk-based screening for those who are in need. Since diagnostic performance of various imaging modalities may vary across subjects, applying the most accurate modality to the patients who would benefit the most requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…All the nine studies related to movement disorders involved patients with Parkinson's disease (PD). Classification of Parkinson's patients versus healthy controls was performed in three studies [133,134,135] with some differences in the reference standard for the disease (sTable 7 in our supplementary document). One study by Liu et al [136] involved the identification of a biomarker through feature selection using the United Kingdom brain bank criteria for diagnosis.…”
Section: Movement Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…All the nine studies related to movement disorders involved patients with Parkinson's disease (PD). Classification of Parkinson's patients versus healthy controls was performed in three studies [133,134,135] with some differences in the reference standard for the disease (sTable 7 in our supplementary document). One study by Liu et al [136] involved the identification of a biomarker through feature selection using the United Kingdom brain bank criteria for diagnosis.…”
Section: Movement Disordersmentioning
confidence: 99%
“…Of the eight studies that performed classification, SVMs were used in seven [133,134,137,138,139,140,141] and LR was used in one study [135]. One study [136] performed feature selection and used Folded concave penalized model for the same.…”
Section: Movement Disordersmentioning
confidence: 99%
“…2,3 Our goal is different in that we focus on subgroup-specific biomarkers for detecting diseases at the earliest possible stage before treatments or even any clinical symptoms begin. The closest relevant work by Liu et al 4 identified subgroup-specific biomarkers by maximizing the absolute mean difference of the biomarkers. However, their distance-based criteria was less commonly used for evaluating biomarkers in practice.…”
mentioning
confidence: 99%